Enhancing drought tolerance in Pisum sativum and Vicia faba through interspecific interactions with a mixed inoculum of Rhizobium laguerreae and non-host beneficial rhizobacteria - Hami, Asma; El Attar, Imane; Mghazli, Najoua; Ennajeh, Salah; Ait-Ouakrim, El Houcine; Bennis, Meryeme; Oulghazi, Said; Badaoui, Bouabid; Aurag, Jamal; Sbabou, Laila; Taha, Kaoutar (Frontiers in Plant Science, 2025)
IntroductionHarnessing plant growth-promoting rhizobia presents a sustainable and cost-effective method to enhance crop performance, particularly under drought stress. This study evaluates the variability of plant growth-promoting (PGP) traits among three strains of Rhizobium laguerreae LMR575, LMR571, and LMR655, and two native PGP strains Bacillus LMR698 and Enterobacter aerogenes LMR696. The primary objective was to assess the host range specificity of these strains and their effectiveness in improving drought tolerance in three legume species: Pisum sativum, Vicia faba, and Phaseolus vulgaris.MethodsIn-vitro experiments were conducted to assess the PGP traits of the selected strains, including phosphate solubilization, indole-3-acetic acid (IAA) production, and siderophore production. Greenhouse trials were also performed using a mixed inoculum of performing strains to evaluate their effects on plant physiological and biochemical traits under drought conditions.ResultsSignificant variability in PGP traits was observed among the strains. R. laguerreae LMR655 exhibited the highest phosphate solubilization (113.85 mg mL-1 PO42-), while R. laguerreae LMR571 produced the highest IAA concentration (25.37 mg mL-1). E. aerogenes LMR696 demonstrated 82% siderophore production. Symbiotic interactions varied, with R. laguerreae LMR571 and LMR655 forming associations with P. sativum and V. faba, but none establishing compatibility with P. vulgaris. Greenhouse experiments showed that a mixed inoculum of R. laguerreae LMR571, LMR655, and E. aerogenes LMR696 significantly improved proline, total soluble sugars, proteins, and chlorophyll content under drought stress, with V. faba showing the strongest response.DiscussionThese findings highlight the importance of strain selection based on host specificity and PGP potential. The enhanced drought tolerance observed suggests that tailored microbial inoculants can improve legume resilience in water-limited environments. This study provides valuable insights for optimizing bioinoculant formulations to enhance crop performance under drought stress.